Martial masculinities : experiencing and imagining the military in the long nineteenth century - Brown, Michael, 1977-; Barry, Anna Maria; Begiato, Joanne (Cultural history of modern war., 2019)
This collection explores the role of martial masculinities in shaping nineteenth-century British culture and society.